2024
DOI: 10.3390/nitrogen5010014
|View full text |Cite
|
Sign up to set email alerts
|

Do the Leaves of Multiple Invasive Plants Decompose More Easily than a Native Plant’s under Nitrogen Deposition with Different Forms?

Chuang Li,
Yue Li,
Shanshan Zhong
et al.

Abstract: This study aimed to clarify the differences in the decomposition rates, soil carbon and nitrogen contents, soil enzyme activities, and the structure of the soil bacterial community between the four Asteraceae invasive plants (AIPs), Bidens pilosa L., Conyza canadensis (L.) Cronq., Solidago canadensis L., and Symphyotrichum subulatum (Michx.) G.L. Nesom, and the native plant Pterocypsela laciniata (Houtt.) Shih under the artificially modeled nitrogen with four forms (including nitrate, ammonium, urea, and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
2
1
Order By: Relevance
“…These observations are also inconsistent with the results of previous research which has shown that invasive plants either degrade more rapidly [18][19][20][21], or significantly more slowly than native plants [58][59][60]. This phenomenon may be due to the similar proportions of soluble and recalcitrant components in the litter of the two trees [28]. In other words, the two trees had similar litter quality, probably because they coexist in the same habitat and have similar growing seasons, growing environments, and lifestyles.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…These observations are also inconsistent with the results of previous research which has shown that invasive plants either degrade more rapidly [18][19][20][21], or significantly more slowly than native plants [58][59][60]. This phenomenon may be due to the similar proportions of soluble and recalcitrant components in the litter of the two trees [28]. In other words, the two trees had similar litter quality, probably because they coexist in the same habitat and have similar growing seasons, growing environments, and lifestyles.…”
Section: Discussioncontrasting
confidence: 91%
“…Previous studies also showed that invasive plants can increase [65,66,68,69] or decrease soil enzyme activities [48,[70][71][72], or have no significant on soil enzyme activities [67,[73][74][75]. Thus, the effects of invasive plants on soil enzyme activities may be species-dependent [28,76] and N-form-dependent [48,77], mainly due to the differences in soil physicochemical properties and the level of available soil nutrients under different plant species and/or different forms of N.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation